2021
DOI: 10.3390/jcm10143196
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Lung Ultrasound Follow-Up in Patients Who Had Recovered from Coronavirus Disease 2019: Results from a Prospective Study

Abstract: There is growing evidence regarding the imaging findings of coronavirus disease 2019 (COVID-19) in lung ultrasounds, however, their role in predicting the prognosis has yet to be explored. Our objective was to assess the usefulness of lung ultrasound in the short-term follow-up (1 and 3 months) of patients with SARS-CoV-2 pneumonia, and to describe the progression of the most relevant lung ultrasound findings. We conducted a prospective, longitudinal and observational study performed in patients with confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
4
16
0
3
Order By: Relevance
“…Prior prospective studies investigating the serial changes in LUS findings during and after a COVID-19 infection, have reported similar findings regarding the gradual decrease in pathologic LUS findings from hospitalization to follow-up 1–4 months after discharge [ 35 , 38 ]. However, the proportion of patients with pathologic LUS findings post-discharge was higher in these serial LUS studies [ 35 , 38 ] as well as in another non-serial LUS study among COVID-19 survivors [ 34 ] compared to ours.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Prior prospective studies investigating the serial changes in LUS findings during and after a COVID-19 infection, have reported similar findings regarding the gradual decrease in pathologic LUS findings from hospitalization to follow-up 1–4 months after discharge [ 35 , 38 ]. However, the proportion of patients with pathologic LUS findings post-discharge was higher in these serial LUS studies [ 35 , 38 ] as well as in another non-serial LUS study among COVID-19 survivors [ 34 ] compared to ours.…”
Section: Discussionmentioning
confidence: 56%
“…Our study may have been underpowered to detect a statistically significant difference between the follow-up LUS findings in patients with and without ARDS during the hospitalization. A prior study in hospitalized COVID-19 patients found that the improvement in LUS score at follow-up post-discharge was greater for those who did not have ARDS during the hospitalization compared to those who had varying degrees of ARDS during the hospitalization [ 35 ]. Thus, patients who have had ARDS may develop more persistent lung changes detectable on LUS at least 2–3 months after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LUS has proved its efficiency in the dynamic monitoring of COVID-19 pneumonia, as well as in the follow-up of patients recovered from this infection [ 63 , 64 ]. Moreover, a recent review proves the usefulness of hand-held ultrasound equipment, which has the advantage of lower acquisition costs and that is easy to decontaminate, which is a necessary activity nowadays [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third and finally, it shows how the use of POCUS allows for a faster diagnosis and quick detection of complications in both hospitalised and ambulatory patients, which leads to earlier and more directed treatment of these conditions that during the current pandemic is more important than ever before. 7 8 …”
Section: Descriptionmentioning
confidence: 99%